History in Documents, VOC Records from Batavia (17-18th Centuries) - Katkova, Irina (Manuskripta, 2023)
The present article deals with Malay letters and documents from the archives of the Dutch East India Company (Verenigde Oost-Indische Compagnie– VOC), dating to the seventeenth and eighteenth centuries. The documents belong to the collection of the Russian scholar and collectioner N.P. Likhachev (1862-1936) and have been kept in the Institute of Oriental Manuscripts in St.Petersburg since 1938. The collection of VOC diplomatic letters that was in a possession of to Governor-General Johan van Hoorn (1653-1711), travelled from old Batavia, to Amsterdam and then to St. Petersburg. Fifty-six letters were written in different languages, Malay in Arabic and Javanese scripts, Dutch, Persian, Arabic, Spanish and Chinese. Mostly addressed to Johan van Hoorn the Dutch Governor-General in 1704-1709, they are not only exemplary of the fine art of Malay letter-writing, but also original diplomatic documents and historical sources on Dutch early colonial policy in Malay Archipelago. === Artikel ini membahas surat-surat Melayu dan dokumen-dokumen dari arsip Perusahaan Hindia Timur Belanda (Verenigde Oost-Indische Compagnie– VOC), yang berasal dari abad ketujuh belas dan kedelapan belas. Dokumen- dokumen tersebut milik koleksi akademisi dan profesor asal Rusia N. P. Likhachev (1862-1936) dan disimpan di Institute of Oriental Manuscripts di St. Petersburgsejak tahun 1938. Koleksi surat-surat diplomatik VOC yang dimiliki oleh Gubernur Jenderal Johan van Hoorn (1653-1711), berasal dari Batavia lama, ke Amsterdam dan kemudian ke St. Petersburg. Lima puluh enam surat ditulis dalam berbagai bahasa, Melayu dalam aksara Arab dan Jawa, Belanda, Persia, Arab, Spanyol, dan Cina. Sebagian besar ditujukan kepada Johan van Hoorn, Gubernur Jenderal Belanda pada tahun 1704-1709, karya-karya tersebut tidak hanya merupakan contoh seni penulisan surat Melayu, namun juga dokumen diplomatik asli dan sumber sejarah mengenai kebijakan awal kolonial Belanda di Kepulauan Melayu. , , , , .